Mutation Rates and Fitness Genes in Staphylococcus aureus Treated with the Medicinal Plant Synadenium glaucescens - Zaituni Msengwa; Martin Saxtorph Bojer; Frank Rwegoshora; James Mwesongo; Magesa Mafuru; Faith Philemon Mabiki; Beda John Mwang’onde; Madundo Mkumbukwa Mtambo; Lughano Jeremy Kusiluka; Henrik Christensen; Robinson Hammerthon Mdegela; John Elmerdahl Olsen (Applied Sciences)
Extracts, fractions and the pure compound epifriedelanol of the medicinal plant Synadenium glaucescens have antibacterial properties. Herbal products are generally considered less prone to resistance development than conventional antimicrobials, as they contain multiple compounds, which makes bacteria less likely to develop resistance. However, data supporting this notion are lacking. This study evaluated the development of resistance in Staphylococcus aureus subjected to extract, fractions and epifriedelanol of S. glaucescens. It also identified S. aureus fitness genes contributing to intrinsic resistance to extract of S. glaucescens. Fluctuation and gradient concentration assays were used to determine mutation rates and growth adaptation, respectively, which were lower following exposure to growth in crude extract than the pure compound epifriedelanol. By subjecting 1920 single gene mutants from the Nebraska Transposon Mutant Library to growth in the presence of extract of S. glaucescens, 12 genes were identified as important for natural resistance in S. aureus JE2; however, only mutation in the hemB gene decreased the minimum inhibitory concentration by greater than 4-fold (64-fold). In conclusion, purifying active antimicrobial compounds from S. glaucescens and using them as antibacterial substances as an alternative to crude extract increased the risk of resistance development. Further, the gene hemB appears to have a significant role in the natural resistance to the extracts obtained from S. glaucescens in this study.